Sustainability is good business for agriculture - Institute of Agricultural and Forest Management and Certification (2016)
This issue of Sustentabilidade em Debate brings together three studies that complement each other with the aim of answering the same question: can the adoption of good management practices for production, conservation of natural resources and working conditions be justified economically? In other words, is the adoption or pursuit of sustainability a good deal for farmers? This question stems from a mismatch between common sense and the experience of Sebrae-MG’s Educampo Program, Rabobank and Imaflora with a large number of farmers. As a rule, industry leaders argue that sustainability can be achieved as long as someone foots the bill. This statement embeds the assumption that sustainability is a cost or a competitive disadvantage. The experience of leading organizations in these studies shows otherwise. Farmers affected by programs that contribute to the implementation of sustainability initiatives have reported that investments in agricultural production based on best practices bring economic returns and make their businesses more profitable, competitive and resilient. To test whether this perception is actually true, SEBRAE, Rabobank and Imaflora joined researchers from ESALQ-USP and from the University of Oxford. Based on robust methods, the three studies analyzed large databases that contain information from dozens of farmers covered by programs designed to stimulate sustainability in several regions of Brazil either through the provision of credit, technical assistance or certification. This publication presents, in advance and in a simplified and summary form, studies in final stages of postgraduate research that will later be published in detailed academic format. The main conclusions and recommendations of the studies are the following ones: 1. Farmers who adopt sustainability and management programs have improved economic performance outcomes. They are, therefore, more competitive. 2. This is because these farmers achieve higher productivity, become more efficient and produce at a lower cost. The economic advantages enjoyed on the farms are independent from market benefits or special prices. 3. A farmer with high socioenvironmental performance tends to have greater financial health and, therefore, would tend to be a customer with less risk and greater ability to pay for the financial sector. 4. A management system is critical for implementing sustainability practices and for improving productivity and the efficiency of production. 5. Management systems and sustainability practices can be adopted by small, medium and large farmers. Collective actions favor and increase the scale of adoption for small and medium ones. We have not found any dependence between socioenvironmental performance and the wealth or size of farmers. 6. Credit can influence the adoption and support the implementation of good practices, management systems and sustainability practices in agriculture. A credit policy based on incentives and mechanisms for supporting changes driven by financial agents can induce a process of continuous improvements in the performance of farmers in terms of sustainability. The adoption of such a mechanism tends to be beneficial for farmers and banks. 7. Market instruments such as certification contribute to the implementation of management systems and sustainability practices. They can be implemented collectively, thus reducing costs for farmers. 8. There is a gap in terms of public policies designed to support the adoption of better management systems by farmers. Weak technical assistance and rural extension programs constitute a major barrier to sustainability. 9. The experiences of Rabobank and of the Educampo program (SEBRAE) show the potential of credit and technical assistance to promote and support the implementation of sustainability practices on farms. However, the main public policies for agricultural production do not encourage or support the implementation of management systems and sustainability practices as a core component. Little by little, sustainability parameters are being incorporated into some policies, but still in a marginal way. The metrics of production and productivity that usually measure the sector's success make all the challenges and complexities involved in promoting sustainable production invisible. 10. Weak public technical assistance and rural extension (ATER) programs go hand in hand with the increasing role of the private sector as a source of innovation and technology transfer, which is not necessarily intended to improve management systems, sustainability practices and the efficiency of farmers.